Agronegocios lecheros y transformaciones territoriales. Los casos de Argentina y Ecuador - Zamboni, Virginia (Universidad Nacional del Litoral, 2022)
During the process of globalization, rural territories suffer different types of destructuring depending on the degree of advancement of the processes of commodification of these spaces. At the global level, milk production constitutes a strategic element for the consolidation of agroindustrial capital. Currently, Latin America is the leading continent in terms of milk powder production and the third in terms of milk production (FAO, 2011). In this region, although milk is mostly produced by small and medium farmers, processing, industrialization and marketing depend on logics dominated by large agribusinesses. The article presented here aims to compare the reality of two countries, Argentina (second largest producer in the region) and Ecuador (fifth largest producer in the region), in order to understand the transformations generated in rural territories and how the expansion strategies of agroindustrial capital are also modified by the multiple responses coming from peasant economies.